DC Bus Overcurrent Protection Scheme in Metro DC Traction Power Supply System Based on Boolean Logic Calculation - LIU Yuxing; ZHENG Chunchun; LAI Peixin; XIE Jinlian; XIE Yuehai; LIU Yajie (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] To enable accurate determination of DC (direct current) bus overcurrent protection in metro DC traction power supply system and enhance the selectivity of fault tripping in the system, the research on a suitable DC bus overcurrent protection scheme is required without increasing equipment or current sampling circuits. [Method] The current direction and protective operation status of various circuits connected to the DC bus are analyzed under various operating conditions of metro DC traction power supply system. Boolean logic calculations are used to extract and refine the logical basis for bus overcurrent protection. An engineering implementation scheme based on GOOSE (generic object-oriented substation event) information exchange is proposed, with an extension of the logical nodes for DC bus overcurrent protection. A circular network test platform based on HSR (high-availability seamless redundancy) is constructed to simulate and analyze the following four scenarios of DC power supply system: normal operation, bus fault, upstream fault on the DC incoming line, and DC feeder fault. [Result & Conclusion] The proposed scheme could determine bus faults by detecting forward overcurrent protection actions on incoming and outgoing lines of the DC bus. It meets the requirements for protection reliability and speed, offering a DC bus protection solution that integrates low cost, high reliability, and simple implementation. The scheme ensures reliable tripping for bus faults and satisfies the selectivity and rapid response requirements of protection devices.